1987
DOI: 10.1161/01.res.60.5.747
|View full text |Cite
|
Sign up to set email alerts
|

Vagal mediation of the effects of atrial natriuretic factor on blood pressure and arterial baroreflexes in the rabbit.

Abstract: We investigated the hemodynamic effect of synthetic atrial natriuretic factor Auriculin A (ANF) and its influence on arterial baroreflex control of heart rate, systemic blood pressure, and perfuslon pressure in the hind limb (perfused at constant flow) in rabbits anesthetized with a-chloralose and urethane. The neural mechanisms underlying these effects were also studied. In the intact animal, a 45-minute constant infusion of ANF (2 /xg/kg prime, 0.2 /ig/kg/min) significantly reduced mean blood pressure and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…In the present study, we found no significant correlation between a decrease of BRS and overactivation of sympathetic nervous system, but a direct relationship was observed between a low BRS and an increased ANP level. Our observational relationship between BRS and ANP was consistent with the recent observation of Volpe 25 and the study of Ebert 27 with exogenous administration of ANP, suggesting a restoration of the impairment BRS with ANP. We could not find any significant relationship between BRS and catecholamines, which might be explained by the fact that our heart failure patients were relatively mild and stable, and that ANP is the most sensitive neurohumoral factor indicating the severity of heart failure.…”
Section: Relationship Between Brs and Humoral Factors In Heart Failuresupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, we found no significant correlation between a decrease of BRS and overactivation of sympathetic nervous system, but a direct relationship was observed between a low BRS and an increased ANP level. Our observational relationship between BRS and ANP was consistent with the recent observation of Volpe 25 and the study of Ebert 27 with exogenous administration of ANP, suggesting a restoration of the impairment BRS with ANP. We could not find any significant relationship between BRS and catecholamines, which might be explained by the fact that our heart failure patients were relatively mild and stable, and that ANP is the most sensitive neurohumoral factor indicating the severity of heart failure.…”
Section: Relationship Between Brs and Humoral Factors In Heart Failuresupporting
confidence: 92%
“…Volpe et al reported that ANP sensitized vagal afferents and that it exerted a selective influence on baroreflex responses to hypertensive stimuli. 25 In the rat, it has also been reported that reflex tachycardia and sympathoexcitation did not occur during hypotension caused by ANP, whereas similar levels of hypotension produced with nitroglycerin provoked an appropriate reflex tachycardic response. 23,24 Vagotomy did reverse these inhibitory effects of ANP, but atropine did not.…”
Section: Influence Of Anp On Brsmentioning
confidence: 93%
See 1 more Smart Citation
“…Ferrari et al 1 considered the possibility that ANF increased vagal influences on the heart. Volpe et al 7 came to the same conclusion with the findings that ANF potentiated reflex bradycardia, and this effect of ANF was prevented by vagotomy and atropine. However, there are questions to be answered in this regard.…”
mentioning
confidence: 52%
“…However, there are questions to be answered in this regard. First, Volpe et al 7 noted that increases in resting heart rate caused by vagotomy and atropine were small and comparable before and after intravenous ANF. The latter results appear to contradict the suggestion of increased resting vagal activity induced by ANF.…”
mentioning
confidence: 99%